Ultrahigh-pressure metamorphism of crustal rocks from the Rhodope metamorphic province: evidence from coesite, diamond and majoritic garnet in eclogites and metapelites - MPOSKOS, E.; KOSTOPOULOS, D. (Bulletin of the Geological Society of Greece, 2001)
The Rhodope Metamorphic Province represents an area of continental collision between the Balkan domain to the north and the Pangaeon domain to the south. Today, exposed astride the suture zone are Palaeozoic and Mesozoic protoliths of both continental and oceanic provenance that underwent Alpine deformation and metamorphism in a subduction zone setting. From petrostructural studies the picture that emerged is one of a central, structurally lower, marble-dominated terrain (i.e. a metamorphic core complex), and a surrounding, structurally higher, gneiss-dominated terrain. Here, for the first time, we report the presence of ultrahigh-pressure metamorphic indicator minerals such as coesite, diamond and Si-Ti-Na-P-rich (i.e. majoritic) garnet in amphibolitized eclogites and garnet-biotitekyanite gneisses from localities scattered throughout the structurally higher terrain. These findings, corroborated by optical microscopy, electron microprobe analyses and in situ laser Raman microspectroscopy, suggest that the protoliths of these rocks were dragged down to mantle depths exceeding 200 km. The individual pressure-temperature paths published before for various subunits of the structurally higher terrain should henceforth be regarded as peculiarities of the exhumation path followed by the subunits.